2018
DOI: 10.1016/j.clim.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils and viral-induced neurologic disease

Abstract: Infection of the central nervous system (CNS) by neurotropic viruses represents an increasing worldwide problem in terms of morbidity and mortality for people of all ages. Although unique structural features of the blood-brain-barrier (BBB) provide a physical and physiological barrier, a number of neurotropic viruses are able to enter the CNS resulting in a variety of pathological outcomes. Nonetheless, antigen-specific lymphocytes are ultimately able to accumulate within the CNS and contribute to defense by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Here we identified perivascular neutrophil swarming in response to viral infection in the brain in regions of increased BBB permeability, potentially reflecting remodeling of the extravascular matrix (Kienle and Lä mmermann, 2016). Nevertheless, the impact of neutrophil migration appears to be context dependent, because an inducible astrocyte-specific CXCL1 transgenic model resulted in increased neutrophil migration, which was associated with demyelination, but not a breakdown of the BBB (Marro et al, 2016;Grist et al, 2018). In contrast, in a transgenic model of oligodendrocyte-specific CXCL1 constitutive expression, neutrophil infiltration into the brain was associated with disruption of the BBB and increased mortality without dysmyelination (Tani et al, 1996).…”
Section: Discussionmentioning
confidence: 85%
“…Here we identified perivascular neutrophil swarming in response to viral infection in the brain in regions of increased BBB permeability, potentially reflecting remodeling of the extravascular matrix (Kienle and Lä mmermann, 2016). Nevertheless, the impact of neutrophil migration appears to be context dependent, because an inducible astrocyte-specific CXCL1 transgenic model resulted in increased neutrophil migration, which was associated with demyelination, but not a breakdown of the BBB (Marro et al, 2016;Grist et al, 2018). In contrast, in a transgenic model of oligodendrocyte-specific CXCL1 constitutive expression, neutrophil infiltration into the brain was associated with disruption of the BBB and increased mortality without dysmyelination (Tani et al, 1996).…”
Section: Discussionmentioning
confidence: 85%
“…Functionally, neutrophils have been suggested to play a defensive role [2,3], as depletion of these immune cells leads to higher viral loads and subsequent death in a neurotropic JHM strain of mouse hepatitis viral infection [16] and an increase in viral multiplication and fatality in herpes simplex virus type-1 infection of the murine cornea [17]. In addition, neutrophils have been shown to contribute to the control of viral replication and the severity of neurological diseases [18]. Studies have shown intriguing cytokine effects on neutrophils: IFN-γ and TNF-α induce phagocytosis [19] and the intracellular killing of microorganisms [20].…”
Section: Introductionmentioning
confidence: 99%
“…Infecting animals with coronavirus induced a significant neurological disorder that could be due to the presence of large amounts of the virus, particularly in the hippocampus [34,35]. This process, in turn, can induce an inflammatory brain response with uncontrolled activation of astrocytes (astrogliosis) and infiltration of neutrophils through an inflamed blood-brain barrier [36]. When these changes occur, brain neurons are damaged, including around the hippocampus, which may result in nerve cell degeneration with clinical dementia and cognitive impairment.…”
Section: Potential Pathophysiological Factors Of Delirium In Covid-19mentioning
confidence: 99%